CURRENT STATE AND SOME METHODS OF TREATMENT OF ATHEROSCLEROSIS (Uzbekistan Open Conference, 2025)
Atherosclerosis is currently one of the most common and dangerous diseases of the cardiovascular system. The paper analyzes the mechanisms of atherosclerosis development, its impact on the body, as well as modern treatment methods. Along with traditional therapeutic approaches, the essence and therapeutic advantages of ozone therapy are examined in detail. It is noted that ozone therapy is highly safe and has fewer side effects compared to other pharmacological methods.